2005
DOI: 10.1093/nar/gki790
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent properties of DNA base analogue tC upon incorporation into DNA -- negligible influence of neighbouring bases on fluorescence quantum yield

Abstract: The quantum yield of the fluorescent tricyclic cytosine analogue, 1,3-diaza-2-oxophenothiazine, tC, is high and virtually unaffected by incorporation into both single- and double-stranded DNA irrespective of neighbouring bases (0.17–0.24 and 0.16–0.21, respectively) and the corresponding fluorescence decay curves are all mono-exponential, properties that are unmatched by any base analogue so far. The fluorescence lifetimes increase when going from tC free in solution (3.2 ns) to single- and double-stranded DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
115
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 50 publications
9
115
1
1
Order By: Relevance
“…The tuneability in emission wavelength is very interesting and is potentially useful in fluorescence resonance energy transfer experiments, where the emission wavelength should energetically overlap the absorption of the acceptor. In fact, the energy of the emission of the nucleosides matches the energy of the absorption of our previously characterized base analogues tC/tC O , [7,8] and thus, constitutes promising nucleic acid FRET donor candidates. Because hydrogen bonding often has a strong influence on the fluorescence quantum yield, one of the more promising derivatives 6d was deprotected to yield 7d (Scheme 1), and the photophysical properties of 7d were measured in water.…”
Section: Photophysical Characterisationsupporting
confidence: 62%
See 1 more Smart Citation
“…The tuneability in emission wavelength is very interesting and is potentially useful in fluorescence resonance energy transfer experiments, where the emission wavelength should energetically overlap the absorption of the acceptor. In fact, the energy of the emission of the nucleosides matches the energy of the absorption of our previously characterized base analogues tC/tC O , [7,8] and thus, constitutes promising nucleic acid FRET donor candidates. Because hydrogen bonding often has a strong influence on the fluorescence quantum yield, one of the more promising derivatives 6d was deprotected to yield 7d (Scheme 1), and the photophysical properties of 7d were measured in water.…”
Section: Photophysical Characterisationsupporting
confidence: 62%
“…[4,5] Several fluorescent pyrimidine analogues have been reported, e.g. the tricyclic cytosine analogues 1,3-diaza-2-oxophenothiazine (tC) [6,7] and its oxo analogue tC O , [8] which have high fluorescence quantum yields even after incorporation into single-and doublestranded DNA. Furthermore, the phenylpyrrolocytosine is designed to engage guanine with an additional hydrogen bond [9] as well as the furan-modified pyrimidines that have been shown to detect abasic sites [3] and binding of ligands to RNA.…”
Section: Introductionmentioning
confidence: 99%
“…1). [28][29][30][31][32][33][34][35][36] The tC nucleotide was originally developed as an analog of C with stronger binding to complementary G bases within RNA 37 and was further derivatized with a guanidinium group to form the so-called G-clamp that provides a strong binding affinity for G. [38][39][40] We find that DinB, like the Klenow fragment of DNA Pol I, can add tC triphosphate across from template dG. 28,29 We demonstrate that DinB inserts dGTP faithfully across from tC but cannot extend from the newly generated primer terminus.…”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotides containing tC O were synthesized, purified and characterized in the same manner as for tC which is described elsewhere. [13,15] Unmodified, purified and characterized oligonucleotides, not containing tC O , were purchased from ATDBio Ltd (Southampton, England).…”
Section: Chemicalsmentioning
confidence: 99%
“…[10,11] Also, we have shown that tC O on average has a slightly stabilizing effect on DNA duplexes but that, with an intelligent choice of nucleobases surrounding tC O , the melting temperature can be virtually unaffected. [10] Like all other fluorescent base analogs except tC [12,13] quantum yield that is sensitive to hybridization and the nature of the surrounding bases (0.14 b ϕ f b 0.41) [10]. However, tC O preserves significantly more of its high fluorescence quantum yield upon hybridization than any other of these base analogs.…”
Section: Introductionmentioning
confidence: 96%